ANALISIS KESALAHAN KONSEPTUAL PADA MATERI PENJUMLAHAN DAN PENGURANGAN SISWA KELAS II SDI BERTINGKAT KELAPA LIMA 3 BERDASARKAN TEORI NEWMAN - Sisilia Hadin; Rince S.M Benu (STKIP Subang, 2026)
This study aimed to describe the forms of students’ conceptual errors in addition and subtraction material in Grade II of SDI Bertingkat Kelapa Lima 3 based on Newman Analysis. Conceptual errors in mathematics learning are one of the common problems experienced by elementary school students because they can affect the understanding of basic concepts in subsequent learning materials. Newman Analysis was used to identify students’ errors through five stages, namely reading, comprehension, transformation, process skills, and encoding. This study employed a qualitative approach with a descriptive research design. The participants of this study were Grade II students of SDI Bertingkat Kelapa Lima 3 and the Grade II classroom teacher. Data were collected through written tests, observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. Data validity was ensured through technique triangulation and source triangulation. The results showed that students made errors at all stages of Newman Analysis. At the reading stage, some students still made mistakes in recognizing mathematical symbols and key words in the questions. At the comprehension stage, students had not fully understood the meaning of the questions. At the transformation stage, students made mistakes in determining the appropriate mathematical operation. At the process skills stage, students still made errors in carrying and borrowing techniques. At the encoding stage, students had not written the final answers according to the context of the questions. The most dominant errors were found at the process skills stage because students still lacked understanding of the correct calculation procedures.